Recreational microplastics as emerging pollutants: effects of crumb rubber leachate across ecosystems - Sharon T. Pochron; Xiayan Ye; Amith S. Maroli; Arjun K. Venkatesan; Samy Sasoun; Thomas J. Gaylor; Mary Girgis; Morgan A. Jacobellis; Alec Miranda; Johanna A. Mitra; Grace Van Gelder; Samantha H. Byrne; et al. (Chemosphere, 2026)

Review and Synthesis: Peatland and Wetland Models Simulating CH4 Production, Oxidation and Transport Pathways - Amey Sudhir Tilak; Alina Premrov; Ruchita Ingle; Nigel Roulet; Benjamin R. K. Runkle; Matthew Saunders; Avni Malhotra; Kenneth A. Byrne (Wetlands, 2026)
Peatlands play an important role in the global methane (CH 4 ) cycle and models are key tools to assess global change effects on CH 4 processes. It remains unclear how well existing wetland modelling frameworks are suited to peatland questions. Therefore, we reviewed the published literature on 16 peatland and wetland models and reported spatial and temporal scales, spin-up periods for stabilization of different carbon pools, and various CH 4 production, oxidation and transport processes. Based on the information derived from the published literature, but without simulating any of the reviewed models and therefore without using a common assessment criterion, we summarized model benefits and challenges, common and unique model specific inputs, and inputs impacting CH 4 plant-mediated transport, diffusion and ebullition. Also, using the information derived from the published literature, the 16 reviewed models were distinguished into five categories with respect to varying degrees of process representation related to CH 4 production, oxidation and transport. We found the models that exhibited the full to adequate process representation regarding CH 4 production and oxidation are Ecosys, CLM-Microbe, ELM-Spruce, Peatland-VU, Wetland-DNDC, TEM-MDM, TRIPLEX-GHG, and CLM4Me. This literature review indicates that existing models are adequate for site-level CH 4 flux assessments, but their predictive power for CH 4 production, oxidation and transport processes remain unclear, until all reviewed models are simulated using a common assessment criterion. Overall, this review study provides a roadmap for selecting peatland and wetland models for early career researchers, first time/new modelers and non-expert modelers seeking literature published information on the available peatland and wetland models simulating CH 4 production, oxidation and transport processes.

Techno-Economic assessment of Energy–Optimised grass biomethane and biofertilizer production simulated with Aspen plus and pinch technology - Milad Motaghi; Pedram Vousoughi; Abolghasem Kazemi; David Styles; Kenneth A. Byrne (Bioresource Technology, 2026)

Environmental assessment of anaerobic digestion within net-zero and policy-aligned AFOLU sector futures - Pedram Vousoughi; Andres Martinez Arce; George Bishop; Daniel Henn; Colm Duffy; David Styles; Kenneth A. Byrne (Journal of Cleaner Production, 2026)

Comparing light and dark chamber measurements of CH4 fluxes in drained and rewetted raised bogs of Ireland - Stephen Barry; Kenneth A. Byrne; Kenneth Crawford; Michael A. Clancy; Clare O’Doherty; Grainne Heagney; Harry Kelly; Mark McCorry; Hannah Mealy; Brian Mollahan; Matthew Saunders; Amey S. Tilak (Wetlands Ecology and Management, 2025)

Introducing ‘miniRECgap’ R package for simple gap-filling of missing eddy covariance CO2 flux measurements with classic nonlinear environmental response functions via GUI-supported R-scripts (case-study: In-sample gap-filling with ‘miniRECgap’ vs. MDS and an optimised shallow ANN in a ‘challenging’ peatland ecosystem) - Alina Premrov; Jagadeesh Yeluripati; Richard Slevin; Adam Bates; Magdalena Matysek; Stephen Barry; Kenneth A. Byrne; Rowan Fealy; Bernard Hyde; Gary Lanigan; Mark McCorry; Rachael Murphy; et al. (Environmental Modelling & Software, 2025)

Exploring the frontier of bovine protein production within territorial net zero emission targets - Daniel Henn; Colm Duffy; James Humphreys; James Gibbons; Emma Buckley; Kenneth A. Byrne; David Styles (Science of The Total Environment, 2025)

The identification and quantification of tire and road wear particles in Osaka Bay, Japan, by two analytical methods - Timothy R. Barber; Francisca Ribeiro; Sophie Claes; Yuya Kawamura; Jamie Yeung; Harriet A. Byrne; Steffen Weyrauch; Thorsten Reemtsma; Kenneth M. Unice (Marine Pollution Bulletin, 2025)

Active afforestation of drained peatlands is not a viable option under the EU Nature Restoration Law - Gerald Jurasinski; Alexandra Barthelmes; Kenneth A. Byrne; Bogdan H. Chojnicki; Jesper Riis Christiansen; Kris Decleer; Christian Fritz; Anke Beate Günther; Vytas Huth; Hans Joosten; Radosław Juszczak; Sari Juutinen; et al. (Ambio, 2024)
The EU Nature Restoration Law (NRL) is critical for the restoration of degraded ecosystems and active afforestation of degraded peatlands has been suggested as a restoration measure under the NRL. Here, we discuss the current state of scientific evidence on the climate mitigation effects of peatlands under forestry. Afforestation of drained peatlands without restoring their hydrology does not fully restore ecosystem functions. Evidence on long-term climate benefits is lacking and it is unclear whether CO 2 sequestration of forest on drained peatland can offset the carbon loss from the peat over the long-term. While afforestation may offer short-term gains in certain cases, it compromises the sustainability of peatland carbon storage. Thus, active afforestation of drained peatlands is not a viable option for climate mitigation under the EU Nature Restoration Law and might even impede future rewetting/restoration efforts. Instead, restoring hydrological conditions through rewetting is crucial for effective peatland restoration.

Cattle production strategies to deliver protein with less land and lower environmental impact - Daniel Henn; Colm Duffy; James Humphreys; James Gibbons; Kenneth A. Byrne; David Styles (Journal of Environmental Management, 2024)

Soil organic carbon stocks by soil group for afforested soils in Ireland - Caren Jarmain; Thomas Cummins; Antonio Jonay Jovani-Sancho; Tim Nairn; Alina Premrov; Brian Reidy; Florence Renou-Wilson; Brian Tobin; Kilian Walz; David Wilson; Kenneth A. Byrne (Geoderma Regional, 2023)

Soil carbon balance of afforested peatlands in the maritime temperate climatic zone - Antonio Jonay Jovani‐Sancho; Thomas Cummins; Kenneth A. Byrne (Global Change Biology, 2021)
Drainage and conversion of natural peatlands to forestry increases soil CO 2 emissions through decomposition of peat and modifies the quantity and quality of litter inputs and therefore the soil carbon balance. In organic soils, CO 2 net emissions and removals are reported using carbon emission factors (EF). The choice of specific default Tier 1 EF values from the IPCC 2013 Wetlands supplement depends on land‐use categories and climate zones. However, Tier 1 EF for afforested peatlands in the temperate maritime climate zone are based on data from eight sites, mainly located in the hemiboreal zone, and the uncertainty associated with these default values is a concern. In addition, moving from Tier 1 to higher‐Tier carbon reporting values is highly desirable when large areas are affected by land‐use changes. In this study, we estimated site‐specific soil carbon balance for the development of Tier 2 soil CO 2 ‐C EFs for afforested peatlands. Soil heterotrophic respiration and aboveground tree litterfall were measured during two years at eight afforested peatland sites in Ireland. In addition, fine‐root turnover rate and site‐specific fine‐root biomass were used to quantify belowground litter inputs. We found that drainage of peatlands and planting them with either Sitka spruce or lodgepole pine, resulted in soils being net carbon sources. The soil carbon balance at multi‐year sites varied between 63 ± 92 and 309 ± 67 g C m −2 year −1 . Mean CO 2 ‐C EF for afforested peatlands was 1.68 ± 0.33 t CO 2 ‐C ha −1 year −1 . The improved CO 2 ‐C EFs presented here for afforested peatlands are proposed as a basis to update national CO 2 ‐C emissions from this land‐use class in Ireland. Furthermore, new data from these sites will significantly contribute to the development of more reliable IPCC default Tier 1 CO 2 ‐C EFs for afforested peatlands in the maritime temperate climate zone.

The role of planted forests in the provision of habitat: an Irish perspective - Cormac J. O’Callaghan; Sandra Irwin; Kenneth A. Byrne; John O’Halloran (Biodiversity and Conservation, 2017)

Collar insertion depth effects on soil respiration in afforested peatlands - A. Jonay Jovani-Sancho; Thomas Cummins; Kenneth A. Byrne (Biology and Fertility of Soils, 2017)

Biogenic acidification drives density-dependent growth of a calcifying invertebrate in culture - Benjamin Mos; Maria Byrne; Kenneth L. Cowden; Symon A. Dworjanyn (Marine Biology, 2015)

Vegetation and environmental variation in an Atlantic blanket bog in South-western Ireland - Matteo Sottocornola; Anna Laine; Gerard Kiely; Kenneth A. Byrne; Eeva-Stiina Tuittila (Plant Ecology, 2009)

Land cover change and soil organic carbon stocks in the Republic of Ireland 1851–2000 - James M. Eaton; Nicola M. McGoff; Kenneth A. Byrne; Paul Leahy; Ger Kiely (Climatic Change, 2008)

Methane flux dynamics in an Irish lowland blanket bog - Anna Laine; David Wilson; Gerard Kiely; Kenneth A. Byrne (Plant and Soil, 2007)

Patterns in Vegetation and CO2 Dynamics along a Water Level Gradient in a Lowland Blanket Bog - Anna Laine; Kenneth A. Byrne; Gerard Kiely; Eeva-Stiina Tuittila (Ecosystems, 2007)

Above- and belowground biomass measurements in an unthinned stand of Sitka spruce (Picea sitchensis (Bong) Carr.) - Carly Green; Brian Tobin; Michael O’Shea; Edward P. Farrell; Kenneth A. Byrne (European Journal of Forest Research, 2007)

A high resolution green area index for modelling the seasonal dynamics of CO2 exchange in peatland vascular plant communities - David Wilson; Jukka Alm; Terhi Riutta; Jukka Laine; Kenneth A. Byrne; Edward P. Farrell; Eeva-Stiina Tuittila (Plant Ecology, 2007)

Stand age‐related effects on soil respiration in a first rotation Sitka spruce chronosequence in central Ireland - GUSTAVO SAIZ; KENNETH A. BYRNE; KLAUS BUTTERBACH‐BAHL; RALF KIESE; VIOREL BLUJDEA; EDWARD P. FARRELL (Global Change Biology, 2006)
The effect of stand age on soil respiration and its components was studied in a first rotation Sitka spruce chronosequence composed of 10‐, 15‐, 31‐, and 47‐year‐old stands established on wet mineral gley in central Ireland. For each stand age, three forest stands with similar characteristics of soil type and site preparation were used. There were no significant differences in total soil respiration among sites of the same age, except for the case of a 15‐year‐old stand that had lower soil respiration rates due to its higher productivity. Soil respiration initially decreased with stand age, but levelled out in the older stands. The youngest stands had significantly higher respiration rates than more mature sites. Annual soil respiration rates were modelled by means of temperature‐derived functions. The average Q 10 value obtained treating all the stands together was 3.8. Annual soil respiration rates were 991, 686, 556, and 564 g C m −2 for the 10‐, 15‐, 31‐, and 47‐year‐old stands, respectively. We used the trenching approach to separate soil respiration components. Heterotrophic respiration paralleled soil organic carbon dynamics over the chronosequence, decreasing with stand age to slightly increase in the oldest stand as a result of accumulated aboveground litter and root inputs. Root respiration showed a decreasing trend with stand age, which was explained by a decrease in fine root biomass over the chronosequence, but not by nitrogen concentration of fine roots. The decrease in the relative contribution of autotrophic respiration to total soil CO 2 efflux from 59.3% in the youngest stand to 49.7% in the oldest stand was explained by the higher activity of the root system in younger stands. Our results show that stand age should be considered if simple temperature‐based models to predict annual soil respiration in afforestation sites are to be used.

Stand age-related effects on soil respiration in a first rotation Sitka spruce chronosequence in central Ireland - GUSTAVO SAIZ; KENNETH A. BYRNE; KLAUS BUTTERBACH-BAHL; RALF KIESE; VIOREL BLUJDEA; EDWARD P. FARRELL (Global Change Biology, 2006)

Partitioning of Respiration in an Intensively Managed Grassland - Kenneth A. Byrne; Ger Kiely (Plant and Soil, 2006)